Étude géologique des Andes du Pérou central Contribution à l'étude géologique des Andes n° 1 - Mégard, François (Travaux de l'IFEA, 1978)
This memoir is one of a series describing studies made by French workers in the Andes since 1960. It has been modified during 1975 and 1976 from a thesis presented to the University of Montpellier II in 1973. The study is based on a cross-section of the Peruvian Andes, from the oceanic trench to the subandean zone, passing through Lima, La Oroya and San Ramon. This section, together with a coloured geological map of Central Peru (scale 1/500000) that covers the principal part of the Andes between 10°30''S and 13°S, gives a good picture of the nature of the Central Andes. The Central Andes are the result of the superposition of a late Cretaceous and Tertiary Andean orogene upon a pre-Triassic sialic substratum: they can justly be given the tittle of the type of the "liminal" chains.